Origin of Gliomas - Cahill, Daniel; Turcan, S̨evin (Seminars in neurology, 2018)
Malignant glioma is a common type of brain tumor that remains largely incurable. Although a definitive cell of origin of gliomas remains elusive, numerous population studies, sequencing efforts, and genetically engineered mouse models have contributed to our understanding of the early events that may lead to gliomagenesis. Herein we summarize our current knowledge on the population epidemiology of gliomas, heritable genetic risk factors, the somatic events that contribute to tumor evolution, and mouse models that have shed light on the glioma cell of origin. Future studies will increase our understanding of the sequence of early events within susceptible cells and their niche that trigger the path to malignant transformation. Such knowledge will allow us to design more effective treatment options to control tumor growth or screening methods for early detection.
Gesehen am 26.03.2020